Validity of the multidimensional assessment profile of disruptive behavior in autistic toddlers - Hannah Fipp‐Rosenfield; Jeffrey Grauzer; Megan Y. Roberts; Aaron J. Kaat (Wiley, 2024)
Abstract Objective Early measurement of atypical disruptive behavior within autistic children is critical for later referrals to behavioral screenings, diagnoses, and services. Disruptive behavior in autistic toddlers is often measured using a categorical approach and identifies the presence or absence of behavior. In contrast, dimensional approaches evaluate behavior on a spectrum of typical to atypical by measuring the clinical salience of disruptive behavior. We sought to assess the validity of the Infant/Toddler version of the multidimensional assessment profile of disruptive behavior (MAP‐DB‐IT), a dimensional approach measurement tool, in a sample of autistic toddlers. Methods Autistic toddlers (n = 82, Mage = 33.2 months, SD = 6.28 months) and their mothers received 8 weeks of caregiver‐mediated social communication intervention. Mothers completed the MAP‐DB‐IT and the Infant Toddler Social Emotional Assessment (ITSEA) across three timepoints: before intervention, immediately after intervention, and at 3 months post‐intervention follow‐up. The MAP‐DB‐IT provided scores for three subdomains: temper loss, noncompliance, and aggression (generically or specifically with siblings). Ratings on the MAP‐DB‐IT were compared to the ITSEA using several analytic strategies such as evaluating (a) the internal consistency of the MAP‐DB‐IT domain scores; (b) the convergent validity between the two measures; and (c) its convergent change due to intervention and if this varied by child characteristics. Results The MAP‐DB‐IT demonstrated excellent internal consistency across all four subdomains. We evaluated convergent validity and found positive correlations between the (a) ITSEA externalizing and MAP‐DB‐IT aggression domain, (b) ITSEA externalizing and MAP‐DB‐IT aggression with siblings domain, and (c) ITSEA dysregulation and MAP‐DB‐IT temper loss domain. Conclusion The MAP‐DB‐IT is a valid measurement tool for disruptive behavior in autistic toddlers. Clinicians should consider the use of the MAP‐DB‐IT for young autistic clients presenting with disruptive behavior to (a) discriminate between early developmentally appropriate tantrums from clinically salient dysregulation, and (b) refer to additional behavioral evaluations and services.